Insights into the Formation of Ternary Complexes Among Wheat Starch, Lauric Acid and Protein: Effects of Plasma Pretreatment Times and Protein Types - Bin Niu; Ziyu Wang; Yizhe Yan (Foods)
Starch-lipid-protein ternary complexes have attracted more attention, and physical processing is gradually being applied to their preparation. This study was to understand the effect of atmospheric cold plasma (ACP) pretreatment times (1–4 min) and protein types (whey protein isolate (WPI), soy protein isolate (SPI), and egg white protein isolate (EWP)) on the wheat starch (WS)-lauric acid (LA)-protein ternary complexes. Experimental results indicated that one-minute ACP pretreatment of WS led to the increase in the amylose content to 30.02%, which produced the largest number of WS-LA-protein complexes (CI value of 69.21%, 67.41%, and 62.81% for WS-LA-WPI, WS-LA-SPI, and WS-LA-EWP complexes, respectively), resulting in the most ordered structure and higher enthalpy change. In vitro digestibility results based on starch showed that WS1-LA-protein complexes exhibited the lowest digestibility with the highest resistant starch content of 28.09%, 27.93%, and 27.41% for these three kinds of complexes, respectively. However, when the treatment time for WS was more than 1 min, a downward trend occurred, indicating that ACP pretreatment of WS for 1 min was the most beneficial for forming complexes. PCA results also verified that ACP pretreatment of WS for different times could significantly impact the generation and structure of ternary complexes. Moreover, protein types also affected the formation and physicochemical properties of ternary complexes. Notably, WPI, with the higher emulsifying property, formed a larger number (CI value of 69.21%), more ordered structure (Xv of 10.56%), and higher thermal stability of ternary complexes than SPI and EWP. This study presents a burgeoning technology to regulate the generation, structure, and functional properties of starch-lipid-protein complexes.